Conhecimento e capacitação para a prática legislativa: um estudo sobre as atividades da escola do legislativo de Araraquara - Lazaretti, Paulo Augusto (Universidade Federal de São Carlos, 2019)
The objective of this work was to identify and analyze the activities offered by the Legislative School of the Araraquara and its benefits for citizens and servants. The fact that, every four years, society is faced with an increasing number of candidates seeking for a position of councilor in many Brazilian cities, and realize that there is no adequate preparation for such candidates to perform their functions in a way that to satisfy the population satisfactorily, since they lack, among other things, capacity and political knowledge, was what motivated this research. The Legislative School aims to improve, specialize, train and inform councilors, civil servants and civil society by offering lectures, conducting courses, establishing agreements with public and private universities and specialized institutions. Through bibliographic, field and documentary research, this work seeks a survey of norms, pedagogical activities, political-pedagogical project, main partners, courses, lectures, activities offered since its creation (Law No. 7,964 on June 12, 2013) until the year 2016. to demonstrate the impacts these events have brought to civil servants and society.The results indicate that, in addition to the political training provided by the parliamentary simulation experience, other formative aspects are highlighted in the reports of the graduates, such as analytical capacity, a better understanding of politics and parliamentary activity, and a better quality of services rendered, that there are opinions that the programs have access to the councilmen did not serve to improve the exercise of seeing and did not have continuity for the servants.
Knowledge and training for legislative practice: a study on the activities of the school of the legislative Araraquara
Keywords: Escola de governo; Escola do legislativo; Parlamento jovem; Democracia; Cidadania; Conhecimento; Vereadores; School of government; School of legislative; Youth parliament; Democracy; Citizenship; Knowledge; Aldermen; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS